A history of Richards Bay 1497-1970's in Zululand Annals Vol. iii, Tony Cubbin Mtunzini : A history, from earliest times to 1995 (Volume 1), Albert van Jaarsveld (Historia, 2021)
Local history remains a dynamic meeting place between the man on the street and the discipline of history. The popularity of this field and its potential for academic enterprise has been exploited by numerous researchers at South African universities as well as the Human Sciences Research Council. The spin-offs are now beginning to gain momentum.
Keywords: history of Richards Bay; Zululand; researchers; Human Sciences Research Council